2024
DOI: 10.1021/acs.nanolett.3c04513
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Heterostructures of CsPbBr3 Perovskite Nanocrystals with Post-transition Metal Bismuth

Avijit Patra,
Koushik Jagadish,
N. Ravishankar
et al.

Abstract: The facet chemistry of halide perovskite nanocrystals plays a key role in designing nanoscale epitaxial heterostructures. However, despite significant successes achieved in designing these nanocrystals, their heterostructures with several leading transition metals could not be established yet. Herein, the possible heterostructures of metals beyond transition metals are explored and the epitaxial combinations of soft CsPbBr 3 nanocrystals with the post-transition metal Bi(0) are reported. These heterostructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In addition, the powder XRD patterns and the XPS spectra of these heterostructures are presented in Figure a,b, respectively. In most of the epitaxial CsPbBr 3 perovskite nanocrystal heterostructures, XRD peaks are mostly dominated with CsPbBr 3 perovskite ,,,, and hence, obtaining intense and clear XRD peaks for the metal sulfides part remained indeed difficult. Again, for these heterostructures, the XPS spectra (Figure b) further confirm the presence of Bi­(III) and S­(II) in the PbBi 2 S 4 rod nanocrystal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the powder XRD patterns and the XPS spectra of these heterostructures are presented in Figure a,b, respectively. In most of the epitaxial CsPbBr 3 perovskite nanocrystal heterostructures, XRD peaks are mostly dominated with CsPbBr 3 perovskite ,,,, and hence, obtaining intense and clear XRD peaks for the metal sulfides part remained indeed difficult. Again, for these heterostructures, the XPS spectra (Figure b) further confirm the presence of Bi­(III) and S­(II) in the PbBi 2 S 4 rod nanocrystal.…”
Section: Resultsmentioning
confidence: 99%
“…There are such reports, but again no clear evidence of lattice matching induced epitaxial relations at the junctions are shown in these nanocrystals. ,,,, Hence, the question remained with the selection of appropriate metal sulfides that can form epitaxial heterostructures with halide perovskites. Among other metals, Bi­(III) is seen either incorporated inside the perovskite nanocrystals or epitaxially connected to the specific facet of the CsPbBr 3 nanocrystal as metallic Bi(0) . Hence, bismuth sulfides are explored here as a case study, and importantly, this led to the formation of CsPbBr 3 –PbBi 2 S 4 orthorhombic–orthorhombic dot-rod coupled heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…However, until now, no such structures have been reported, which questions further the feasibility of their formation. On the other hand, a report on CsPbBr 3 with post-transition metal Bi(0) suggested that such nanostructures could be possible and a representative transmission electron microscopic (TEM) image of such epitaxial heterostructure is presented in Figure e . Pb atoms of CsPbBr 3 viewed along [201] and Bi atoms of trigonal Bi(0) viewed along [001] are presented in Figure f and g, respectively.…”
mentioning
confidence: 99%
“…Further, all of the reported epitaxial heterostructures suggest that the bright emission of halide perovskite nanocrystals largely quenched once these are connected with metal(0). For the case of Pt-, Pd- and Bi-, this has been observed for CsPbBr 3 . However, a report on Ag(0) showed the retention of the host emission . For the case of Au, as no such report has been established yet having plasmonic Au epitaxially connected to halide perovskite nanocrystals, the change in the optical properties is still unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation